A Ray of Hope in Outsourcing: Realizing SDG 8 in Yogyakarta City - Ahmad Ramdhani (UIN Siber Syekh Nurjati Cirebon, 2025)
The unemployment rate in Indonesia, particularly among Generation Z, remains relatively high despite showing a decline between 2023 and 2024. A mismatch between workforce skills and industry needs, along with the dominance of the informal sector, are the main causes. This study examines the role of outsourcing, a system of delegating work to third parties, as a government strategy to reduce unemployment in Yogyakarta and its contribution to achieving the Sustainable Development Goal (SDG) 8: decent work and economic growth. Using a qualitative approach, the results indicate that outsourcing provides broader and more flexible employment access for young job seekers. Although it still faces criticism regarding job stability and labor protection, this mechanism has proven to support the creation of new jobs and promote inclusive economic growth. Thus, outsourcing has the potential to become an effective policy instrument in sustainably expanding employment opportunitiesThe unemployment rate in Indonesia, particularly among Generation Z, remains relatively high despite showing a decline between 2023 and 2024. A mismatch between workforce skills and industry needs, along with the dominance of the informal sector, are the main causes. This study examines the role of outsourcing, a system of delegating work to third parties, as a government strategy to reduce unemployment in Yogyakarta and its contribution to achieving the Sustainable Development Goal (SDG) 8: decent work and economic growth. Using a qualitative approach, the results indicate that outsourcing provides broader and more flexible employment access for young job seekers. Although it still faces criticism regarding job stability and labor protection, this mechanism has proven to support the creation of new jobs and promote inclusive economic growth. Thus, outsourcing has the potential to become an effective policy instrument in sustainably expanding employment opportunities